Pearls & Oy-sters: The critical role of histopathology in diagnosing cancer-associated necrotizing CNS vasculitis. (24th April 2018) - Sheehan, Joshua; Tate, Jessica; Mott, Ryan; Geer, Carol; Wolfe, Rachel; Strowd, Roy E.; Guzik, Amy
Abstract : Objective: To highlight the importance of a broad differential and histopathologic confirmation in patients with newly diagnosed cancer with brain lesions atypical for CNS metastasis. Methods: We report 2 cases of biopsy-proven CNS vasculitis in patients undergoing treatment for a newly diagnosed nonmetastatic cancer. Comprehensive medical record review was performed to identify the clinical presentation, representative neuroimaging, histopathologic features, and response to treatment. Results: Patient 1 presented 1 month into induction therapy of malignant vaginal squamous cell carcinoma (stage 3, T2N1M0) with acute episodic left-sided hemiparesis due to seizure activity progressing to severe encephalopathy. Imaging revealed a right frontoparietal lesion while systemic workup was unrevealing. Biopsy demonstrated necrotizing vasculitis. Patient 2 presented 6 months after diagnosis of right breast invasive ductal carcinoma (stage IIa, T2N0M0, estrogen receptor–positive, progesterone receptor–positive, human epidermal growth factor receptor–2 positive) with subacute bifrontal headaches with associated phonophobia. Imaging showed hyperintense lesions involving the right temporoparietal region and systemic workup was unrevealing. Brain biopsy showed a necrotizing vasculitis. Patient 1 was treated with methyprednisolone and plasmapheresis and patient 2 was treated with prednisone. Both patients showed complete resolution of symptoms shortly after treatment and improvement on imaging. Conclusions: These cases highlight the importance of comprehensive evaluation of new brain lesions in patients with nonmetastatic solid tumors. Characteristics of new brain lesions in patients with cancer that should raise suspicion of diagnoses other than brain metastasis include (1) primary malignancy without regional or distant metastasis, (2) imaging without discrete mass-like enhancement, and (3) cortically based location of lesions not at the gray–white matter junction.